The Worldwide Governance Indicators Project : Answering the Critics - Kaufmann, Daniel; Kraay, Aart; Mastruzzi, Massimo (World Bank, Washington, DC, 2012)
The Worldwide Governance Indicators, reporting estimates of six dimensions of governance for over 200 countries between 1996 and 2005, have become widely used among policymakers and academics. They have also attracted some explicit written criticisms. In this short paper the authors synthesize 11 critiques offered by four recent papers. They then refute them as either conceptually incorrect or empirically unsubstantiated.